2019
DOI: 10.1155/2019/5382708
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Suggesting Spontaneous Passage of Stones from Common Bile Duct: A Retrospective Study

Abstract: Background. Common bile duct (CBD) stones are common. However, they are known to pass spontaneously, which obviates the need for ERCP. Aim. The aim of this study is to identify specific predictors for spontaneous passage of CBD stones. Methods. Data was retrospectively collected for all patients who were hospitalized with clinical, laboratory, or ultrasonographic evidence of choledocholithiasis and who underwent magnetic resonance cholangiopancreatography (MRCP) in Hadassah Medical Center between 2005 and 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 15 publications
4
34
2
1
Order By: Relevance
“…In this study, we used the univariate and multivariate logistic regression analysis to determine the predictive factors for CBD stone. Our results revealed that multiple gallbladder stones, the maximal diameter of CBD stone measured by preoperative ultrasonography, preoperative GGT level and DB/TB ratio were independent predictors of CBD stone, which had been reported by previous studies [17][18][19]. * US, Ultrasonography; US Positive indicates that imaging examination revealed CBD stone; CBDD, the value of maximal CBD dimeter measured on the Ultrasonography; ALT, alanine aminotransferase; AST, aspartate aminotransferase; ALP, alkaline phosphatase; GGT, glutamyl transpeptidase; TB, total bilirubin; DB, direct bilirubin; HR, hazard ratio; CI, confidence interval; P-value<0.05 indicates statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we used the univariate and multivariate logistic regression analysis to determine the predictive factors for CBD stone. Our results revealed that multiple gallbladder stones, the maximal diameter of CBD stone measured by preoperative ultrasonography, preoperative GGT level and DB/TB ratio were independent predictors of CBD stone, which had been reported by previous studies [17][18][19]. * US, Ultrasonography; US Positive indicates that imaging examination revealed CBD stone; CBDD, the value of maximal CBD dimeter measured on the Ultrasonography; ALT, alanine aminotransferase; AST, aspartate aminotransferase; ALP, alkaline phosphatase; GGT, glutamyl transpeptidase; TB, total bilirubin; DB, direct bilirubin; HR, hazard ratio; CI, confidence interval; P-value<0.05 indicates statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…The overall incidence of spontaneous passage CBD stones in prior studies was between 21 and 73% [ [9] , [10] , [11] , [12] , [13] , [14] ]. Tranter et al [ 9 ] found that spontaneous passage of CBD stones occurred more commonly in patients with pancreatitis, biliary colic, and cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we generated ROC curve analysis for size of stone and found that stone size of less than 4.85 mm was more likely to pass spontaneously with acceptable sensitivity (81.8%) and specificity (78.9%). However, Khoury et al [ 11 ] found a stone larger than 3.5 mm had low chance to pass spontaneously with acceptable sensitivity (71%) and specificity (69%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallstones may pass into the GI tract spontaneously through the common bile duct, particularly if the stone size is <3.5 mm [ 6 ]. However, a stone can also pass through a biliary-enteric fistula, a complication seen in 0.3–1.5% of all patients with cholelithiasis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%